1942
DOI: 10.1063/1.1723645
|View full text |Cite
|
Sign up to set email alerts
|

Premelting Anomalies of Some Long Chain Normal Paraffin Hydrocarbons

Abstract: The coefficients of thermal expansion of tetradecane, hexadecane, octadecane, and tetracosane have been measured continuously for considerable temperature ranges on both sides of the melting points. The increase of these coefficients in the neighborhood of the melting points is suggestive of an order-disorder mechanism for the transitions. Although the effect is observed to be larger on the solid side of the transition than on the liquid, the latter is interpreted as more significant, since the presence of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…[18]; n = 14, 16: ref. [19]). The specific volumes have been smoothed separately for the odd and the even n-alkanes.…”
mentioning
confidence: 93%
“…[18]; n = 14, 16: ref. [19]). The specific volumes have been smoothed separately for the odd and the even n-alkanes.…”
mentioning
confidence: 93%
“…The relevant parameters of the solid phases are listed in Table 1. It should be noted that the only experimental value for the molar volume of the solid, 389.27 cm 3 /mol at 304.25 K [20], is compatible with our value for the s 1 phase; perhaps the experiments had been made with a subcooled, not equilibrated sample.…”
Section: Tetracosanementioning
confidence: 54%
“…The available results of density measurements can be roughly categorized by the applied measuring principle. Pycnometers (PM) and dilatometers (DM) as independent measuring systems or combinations of both have been applied by the majority of researchers for liquid as well as solid state measurements [62,63,64,65,66,67,68,69]. Liquid state densities have additionally been determined by means of hydrometers (HM) [27,28] and vibrating-element systems (VE) [27,70].…”
Section: Literature Review Of Thermophysical Properties Of Octadecanementioning
confidence: 99%
“…One datapoint of Shlosinger and Bentilla [67] was neglected since it was located in the 2-phase-region.The whole series of solid state data from Seyer et al [62] was removed because of the indicated solid-solid transformation.All data of Würflinger and Schneider [73] were excluded due to the applied inverse method for determining the solid-state density.The data of Müller and Lonsdale [74] were neglected since their results where achieved with X-ray measurements resulting in very high theoretical density calculations based on the distance between the molecules.Liquid state densities from van Hook and Silver [64] were excluded because of incomprehensible corrections in their data.The liquid state data point of McKinney [72] was removed since it was given at a temperature of 25 C which is obviously in the solid state.…”
Section: Preselection Of Datamentioning
confidence: 99%
See 1 more Smart Citation